EFEKTIVITAS PENGGUNAAN RUBRIK ASESMEN IF-AT (IMMEDIATE FEEDBACK ASSESSMENT TECHNIQUE) TERHADAP HASIL BELAJAR - Sofyan Pramono; Undang Rosidin; Abdurrahman - (Jurnal Pembelajaran Fisika, 2013)
The effevtiveness of using assessment rubrics IF-AT (Immediate Feedback Assessment Technique) for the learning outcomes. Teachers in assessing students usually use the conventional way, by using the conventional multiple choice. Assessment in the conventional way deemed less effective, to overcome these problems it is necessary to be given a new assessment techniques, one of which is the assessment rubric IF-AT. The effectiveness of the application of assessment rubrics IF-AT in improving student learning outcomes should be determined by comparing it with the conventional multiple choice (non IF-AT), the research conducted by implementing the use of assessment rubric IF-AT on Archimedes’s law materilas. The results of this research show that there was a significant differences between the classes that use the rubric asesemen IF-AT and Non IF-AT, where the application of the assessment rubric IF-AT is more effective in improving student learning outcomes assessment techniques compared to conventional multiple choice (non-IF-AT).Keywords: effectiveness, assessment, IF-AT (Immediate Feedback Assessment Technique), learning outcomes.